Arterial spin labeling MR imaging aids to identify cortical venous drainage of dural arteriovenous fistulas. Issue 19 (May 2018) - Kang, Ji Hee; Yun, Tae Jin; Rhim, Jong Kook; Cho, Young Dae; Yoo, Dong Hyun; Yoo, Roh-Eul; Kang, Koung Mi; Choi, Seung Hong; Kim, Ji-hoon; Sohn, Chul-Ho; Han, Moon Hee
Abstract : Abstract: Cortical venous drainage (CVD) increases the probability of intracranial hemorrhage and mortality rate of dural arteriovenous fistulas (DAVF). Although digital subtraction angiography (DSA) is the most accurate method to determine CVD in DAVFs, this modality has limitations due to its invasive nature and radiation issues. The purpose of this study was to evaluate the diagnostic utility of arterial spin-labeling perfusion-weighted images (ASL-PWI) to identify CVD in patients with DAVF. The Institutional Review Board of our hospital approved this retrospective study. ASL-PWI features of 22 patients with DAVF were retrospectively reviewed for the presence of bright signal intensity in cortical veins and brain parenchyma. DAVF with bright signal intensity in cortical veins and/or brain parenchyma was regarded as having CVD. Using DSA as a reference standard, sensitivity, specificity, positive predictive value, and negative predictive value of ASL-PWI for detecting CVD were calculated. Based on DSA features, 11 (11/22, 50%) patients were classified as having "aggressive" pattern with CVD. Eleven (11/22, 50%) patients also showed bright signal intensity in cortical veins (9/22, 41%) and/or brain parenchyma (4/22, 18%) on ASL-PWI. The 11 patients who had "Aggressive" pattern on DSA were the same 11 patients who were classified as having "aggressive" pattern on ASL-PWI. ASL-PWI showed perfect diagnostic performance for identifying CVD with sensitivity, specificity, positive predictive value, and negative predictive value of 100% for all. Thus, ASL-PWI could be used as a noninvasive mean to predict the presence of CVD in patients with DAVFs. It has the potential as a screening tool to evaluate DAVF prior to invasive DSA.